All that glitters : a story of friendship, fraud and fine art - Whitfield, Orlando (Pantheon Books, 2024)
"A dazzling insider look at the contemporary art world and the meteoric rise and fall of the seductive, charismatic, utterly amoral young, American art dealer, Inigo Philbrick, told through the eyes of his former partner and set in London, New York, Miami and Vanuatu Orlando Whitfield and Inigo Philbrick met in 2006 at Goldsmiths University where, though total opposites, they became best friends. By 2007, they were art dealing together having formed I&O Fine Art and two years later, upon graduation, were looking for a gallery space. While they continued to work together, Inigo was also taking on work for the prestigious London Gallery, White Cube. Orlando would set up his own gallery with a partner and watch as Inigo quickly immersed himself in a world of private jets, lavish trips, and close multimillion-dollar deals for major clients. To those who did not know, Inigo seemed a brilliant art world hotshot. But underneath the extravagant façade, his complicated financial schemes were unraveling. Monthly interest installments of $150k were left unpaid; calls were dodged; letters from auction houses faked. With debt, lawsuits, and court summons piling up, Inigo went into an inescapable tailspin of lies and subterfuge. By 2019, things had spiraled enough out of control for Inigo to flee to the remote island of Vanuatu, 300 miles off Fiji. There, in 2020, he was arrested by US Marshals and flown to Guam where he was arraigned in a military court and eventually moved to Brooklyn where he was denied bail and sentenced to seven years in prison for over $86 million in fraud. This unique, shocking, and page-turning story is compulsively readable as it sweeps you up in both adventure and downfall. A close-up of two very young players in the contemporary art world who would each pay a big price, in very different ways, make it an irresistible cautionary tale"--